Problematik Penderita Struma Toksik yang Berobat ke RSUD Koja Tahun 1999-2004 - Santoso M; Ndraha S; Surianty Surianty; Astuti Y (Jurnal Kedokteran Meditek, 2004)
Toxic goiter or toxic struma is a condition that shows the enlargement of the thyroid gland with hyperthyroid signs.        This study was conducted to provide data needed by the hospital and community.        This study used the retrospective technics, for all cases of out and in patient visiting theInternal Medicine Polyclinic in RSUD Koja in periode 1999 -2004. All data were obtained from the medical records.        From 69 toxic struma cases in out and in patient of internal Medicine Policlinic, there are 42,03 % toxic struma patient s which mostly 30 -40 years old. There were 79,71% more women patient than men patient. Mostly patients came with the enlargement of the neck (53,62%). There were 42,02% patients had an increased of T 4 thyroid function. Based on the diagnosis, 36,23% are patients suffered from toxic struma , 59,42% patient were treated wit PTU. Mostly patients choosed to use non operative treatment than strumectomy.